Accuracy of cardiac‐induced brain motion measurement using displacement‐encoding with stimulated echoes (DENSE) magnetic resonance imaging (MRI): A phantom study. Issue 3 (31st August 2020) - Nwotchouang, Blaise Simplice Talla; Eppelheimer, Maggie S.; Biswas, Dipankar; Pahlavian, Soroush Heidari; Zhong, Xiaodong; Oshinski, John N.; Barrow, Daniel L.; Amini, Rouzbeh; Loth, Francis
Abstract : Purpose: The goal of this study was to determine the accuracy of displacement‐encoding with stimulated echoes (DENSE) MRI in a tissue motion phantom with displacements representative of those observed in human brain tissue. Methods: The phantom was comprised of a plastic shaft rotated at a constant speed. The rotational motion was converted to a vertical displacement through a camshaft. The phantom generated repeatable cyclical displacement waveforms with a peak displacement ranging from 92 µm to 1.04 mm at 1‐Hz frequency. The surface displacement of the tissue was obtained using a laser Doppler vibrometer (LDV) before and after the DENSE MRI scans to check for repeatability. The accuracy of DENSE MRI displacement was assessed by comparing the laser Doppler vibrometer and DENSE MRI waveforms. Results: Laser Doppler vibrometer measurements of the tissue motion demonstrated excellent cycle‐to‐cycle repeatability with a maximum root mean square error of 9 µm between the ensemble‐averaged displacement waveform and the individual waveforms over 180 cycles. The maximum difference between DENSE MRI and the laser Doppler vibrometer waveforms ranged from 15 to 50 µm. Additionally, the peak‐to‐peak difference between the 2 waveforms ranged from 1 to 18 µm. Conclusion: Using a tissue phantom undergoing cyclical motion, we demonstrated the percent accuracy of DENSE MRI to measure displacement similar to that observed for in vivo cardiac‐induced brain tissue.